Nutrition Profile and Quality of Milkfish Galantine Added By Different Type and Concentration of Liquid Smoke - Fronthea Swastawati; Ima Wijayanti; Suminto Suminto; Dwi Yanuar Budi Prasetyo (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Galantin milkfish is one of the fish diversification products that can be used as a source of nutrition for the community with the specific appearance. To increase the level of product acceptance mainly aroma, liquid smoke is added as a flavoring agent that is safe to consume. This study aimed to determine the effect of the addition of different types of liquid smoke with appropriate concentrations on nutritional profiles (amino acids and fatty acids) and the quality (proximate and hedonic) of galantin milkfish. Experimental design of factorial was used in this research with three different types of liquid smoke, namely redestilation (R), filtration (F), and microencapsulation (M). The concentrations of the three types of liquid smoke usedwere 1% (1), 2% (2), and 3% (3) respectively. The results showed that the influence of the three types of liquid smoke and different concentrations significantly affected the profile of amino acids, fatty acids, moisture content, protein, fat, carbohydrates, energy and hedonic values   of milkfish galantin (p<0.05). The dominant amino acid in the product was  glutamic acid, while the highest EPA and DHA contents were respectively in F1 and M1 treatments. Water content of milk fish galantin was  69.82% -72.75%, protein 14.56% -16.73%, fat 4.03% -6.14%, ash 1.62% -2.84%, carbohydrates 2.86% -3.58%, and energy 111.55-138.90 Kal/100 g. Theresults of the hedonic analysis showed that all the products produced were favored by the panelists.